Economic and Fiscal Determinants of Regional Own-Source Revenue: Evidence from Kapuas Regency (2015–2024) - Yaya; Tuah, Sunaryo N.; Benius (Institut Bisnis dan Informatika Kesatuan, 2025)
In Indonesia's fiscal decentralization framework, many local governments face ongoing challenges in achieving stable and adequate regional revenues despite having greater autonomy to manage economic potential. This study provides an empirical analysis of economic, demographic, and fiscal factors influencing regional own-source revenue during the period 2015–2024. Using time series data and a multivariate regression method, the research examines the effects of gross regional domestic product, population size, number of restaurants, and government spending on regional own-source revenue. Data were obtained from official statistical publications and regional fiscal reports and supported by national-level literature to strengthen contextual interpretation. The findings indicate that economic growth, demographic expansion, and government expenditure have significant impacts on regional own-source revenue, while the restaurant sector also contributes positively as a potential source of revenue enhancement. The study recommends intensifying tax collection, optimizing the role of the restaurant sector, and improving the strategic allocation of government expenditure to strengthen revenue capacity. It further highlights the importance of adaptive fiscal strategies in response to economic transformation and evolving regulatory frameworks over the past decade.